The first major silver crisis in Russia and the Baltic, c. 875-c. 900 - Noonan, Thomas S. (Hikuin, 1985)
It has long been known that, around 970, a sharp decline took place in the export of Islamic silver coins or dirhams to Russia and the Baltic. Furthermore, it has also been established that the importation of dirhams into Russia came to an end about 1015. The cesation of dirham exports into Russia and the Baltic at this time has been connected with what has been called the silver crisis within the Islamic world, i.e., the severe drop in the coinage of silver and the pronounced debasement of those few silver coins which were struck. While scholars have debated the causes as well as the consequences of this silver crisis, and some have even questioned whether it existed, there can be no doubt that the monetary history of Russia and the Baltic were profoundly impacted by the end of dirham imports.